2004
DOI: 10.1021/bi048496a
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structures of Salt-Refolded Forms of the 434-Repressor DNA-Binding Domain in 6 M Urea

Abstract: The N-terminal 63-residue fragment of the phage 434-repressor, 434(1-63), has a well-defined globular fold in H 2 O solution, and is unfolded in 6 M urea at pH 7.5. In this study, 434(1-63) has been refolded by adding either 1.7 M NaCl or 0.47 M NaTFA to the solution in 6 M urea, and the NMR structures of both refolded forms have been determined. The two refolded forms have similar free energies of unfolding and are ∼16 kJ/mol less stable than the protein in H 2 O solution. 434(1-63) refolded with NaCl exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It is possible that, as recently proposed, a large population of proteins still maintained a nativelike tertiary topology under a variety of denaturing conditions. [64][65][66][67][68][69] The broadening and disappearance of NMR peaks observed for many partially folded or even completely unfolded proteins might result from a slight increase of conformational dynamics on the microseconds to milliseconds time-scales, rather than from the highly disordered tertiary topology.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that, as recently proposed, a large population of proteins still maintained a nativelike tertiary topology under a variety of denaturing conditions. [64][65][66][67][68][69] The broadening and disappearance of NMR peaks observed for many partially folded or even completely unfolded proteins might result from a slight increase of conformational dynamics on the microseconds to milliseconds time-scales, rather than from the highly disordered tertiary topology.…”
Section: Discussionmentioning
confidence: 99%
“…Although this effect might explain our findings for saline-treated frogs, salt stabilization was not expressed in urea-treated frogs, which instead maintained levels of CPS I activity during dehydration. Speculation suggests that the much higher uremia in these frogs could account for the disparity, as elevated urea is known to counteract such salt inhibition (Dotsch et al, '95;Cerasoli et al, 2003;Pervushin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that the aromatic cluster on the surface is structurally less organised after rapid cooling, resulting in the formation of the intermediate. 37 Previous studies have indicated that folding intermediates often lack uniquely structured hydrophobic cores. [10][11][12][13][14][15][16][17] However, the present study suggests that this is not the case for the mutant SBD.…”
Section: Transition From the Intermediate To The Native Statementioning
confidence: 99%